2022
DOI: 10.3389/fonc.2022.911426
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics-Based Machine Learning Models for Predicting P504s/P63 Immunohistochemical Expression: A Noninvasive Diagnostic Tool for Prostate Cancer

Abstract: ObjectiveTo develop and validate a noninvasive radiomic-based machine learning (ML) model to identify P504s/P63 status and further achieve the diagnosis of prostate cancer (PCa).MethodsA retrospective dataset of patients with preoperative prostate MRI examination and P504s/P63 pathological immunohistochemical results between June 2016 and February 2021 was conducted. As indicated by P504s/P63 expression, the patients were divided into label 0 (atypical prostatic hyperplasia), label 1 (benign prostatic hyperpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Additionally, the AUC of T2WI was higher than that of ADC in our study, which is different from the findings of several previous studies [ 25 , 31 ]. However, Liu et al observed the same phenomenon as in our research [ 24 ]. The reason might be related to the following points.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, the AUC of T2WI was higher than that of ADC in our study, which is different from the findings of several previous studies [ 25 , 31 ]. However, Liu et al observed the same phenomenon as in our research [ 24 ]. The reason might be related to the following points.…”
Section: Discussionsupporting
confidence: 86%
“…The T2WI-clinic-combined model exhibited an AUC of 0.94, and the T2-methylation-clinic-combined model reached a higher AUC of 0.97. Previous studies have shown the high predictive value of MRI features for prostate cancer, Liu et al used multiphase MRI features to predict P504s/P63 Immunohistochemical Expression and reached an AUC of 0.93, Qiao et al also constructed a prediction model for Gleason grade group with T2 and DWI features, and the AUC of which was 0.92 [ 24 , 25 ]. The same results were observed in our research, which demonstrated greater efficacy in csPCA diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…13 There is a possibility that prostate-associated antigens will be produced as a consequence of abnormalities in the development of prostate epithelial cells. 14 Prostatespecific antigen (PSA)-a secreted protease, prostatespecific membrane antigen (PSMA)-a highly specific membrane antigen found on their plasma membrane, p63a rare positive prostatic adenocarcinoma, and BCL-2 family proteins-essential regulators of pathways involved in cell death are all examples of these antigens. 12 From this study using IHC analysis, the expressions of PSA, P63 and BCL-2 were expressed in 80 retrieved blocks of prostatic tissues with 40 BPH and 40 CaP.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor multi-omics can be combined with predictive machine learning models, which could be the new digital method on the road to precision cancer medicine. In previous studies of biomarkers for tumor types such as lung cancer, glioma, breast cancer, and prostate cancer, radiomics is found to have the potential as a means to non-invasively predict the status of tumor biomarkers [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Radiomics approaches combined with a noninvasive machine learning model with tumor immunohistochemistry could improve treatment selection.…”
Section: Discussionmentioning
confidence: 99%